Qualitative Study of Experiences Using 3 Months Injection Hormonal Contraceptive Devices on Side Effects of Libido Reducing - Cici Krismawati; Nanik Yuliwati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The informants in this study were the reproductive age group of 20-35 years, the group of informants aged over 35 years, the group of informants with a duration of using 3 months of contraceptive injections under 3 years and the group of informants who had used KB injections of 3 months over 3 years and groups who had used injection 3 months. The informants in this study were 10 acceptors at PMB Cici Krismawati in 2022. The results of this study indicate that the symptoms of decreased libido that appear are more common in the group of informants aged over 3 years and the group of informants who have used more than 3 years, while the group of informants of productive age 20-45 years and the group of informants with a duration of 3 months of contraceptive injections under 3 years is rare, the stage of decreased libido that occurs is still a mild stage. The way to deal with decreased libido is that there are those who just give up, communicated with their partners, there are also couples who watch movies as a medium to bring back their libido. PMB is expected to be able to provide comprehensive information to each acceptor, including how to deal with side effects experienced by acceptors.